PENGARUH ECONOMIC VALUE ADDED (EVA), PROFITABILITAS, EARNING PER SHARE (EPS) DAN OPERATING CASH FLOW (OCF) TERHADAP RETURN SAHAM (Studi Empiris Pada Perusahaan Yang Termasuk Dalam Jakarta Islamic In - Tri Anggita Rani (MNJ 16 UMY 309, 2016)
The aim’s this study is to analyze the influence of Economic Value Added (EVA), Profitability, Earning Per Share (EPS), and Operating Cash Flow (OCF) to stock Return on Jakarta Islamic Index listed in Indeesian Stock Exchange Period 2011-2014. In this study, independent variable are Economic Value Added (EVA), Return On Asset (ROA), Return On Equity (ROE), Earning Per Share (EPS), and Operating Cash Flow (OCF), while the dependent variable is stock Return. The sample of this study are Jakarta Islamic Index listed in Indonesia Stock Exchange in the period 2011 to 2014. The sampling technique in this study used purposive sampling method. So the sample of this study are 116 companies and the data were analyzed using multiple linier regression with SPSS 16. The result of this study are Economic Value Added (EVA), Return On Asset (ROA), Return On Equity (ROE), Earning Per Share (EPS), and Operating Cash Flow (OCF), simultaneously have a significant influence to stock returns. While the partial test are Economic Value Added (EVA) has a significant positive influence to stock returns, Return On Asset (ROA) has a significant positive influence to stock returns, Return On Equity (ROE) has no influence to stock return, Earning Per Share (EPS) has a significant positive influence to stock returns, and Operating Cash Flow (OCF) has no influence to stock Return. Keywords: Economic Value Added (EVA), Return On Asset (ROA), Return On Equity (ROE), Earning Per Share (EPS), and Operating Cash Flow (OCF) and Stock Return.